Non-Operative Treatment of 3-Part and 4-Part Proximal Humerus Fractures and its Related Functional Aftermath - Kamran Saeed, Agha Momin, Aqeel Moazzam, Muhammad Saleem Akhtar, Naeem Mehmood Mughal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the functional outcomes of noninvasive treatment for proximal humerus three parts and four parts fracture. Study Design: Prospective-cohort study Place and Duration of Study: Department of Orthopaedics, Sialkot Medical College, Sialkot from 1st January 2021 to 31st March 2022. Methodology: Fifty patients between 56-65 years and radiograpically both anterior and lateral views were taken. There was a follow up plan in each patient at half month, three months, six months and a year with repeated imaging. Oxford-Shoulder Score and EuroQol-5 Dimensions-3 Levels was used for finding primary functional results while secondary functional outcomes were score through Visual Analog Scoring and University of California at Los Angeles Shoulder Score. Results: The mean of the patients was 62.3±5.6 years with more females (70%) than males. Majority of the cases had a high incidence of fall due to feeling low in energy. The comparison of Oxford-Shoulder Score (OSS) and EQ 5D 3L method showed a high significance within each variable. Comparative imaging at follow ups have showed timely fixation of the humerus with non-invasive procedure with improved OSS values. One-year scores for Oxford-Shoulder Score were 33.1 with 95% confidence of interval while it was 0.59 for EQ-5D-3L. Considering the secondary outcomes it was noticed that mean outcomes score of treatment was 32.1 while visual analogue scale (VAS) pain score was 32.1 with 59.2 as VAS satisfaction score. Conclusion: Good functional outcome of displaced 3-part and 4-part fracture of proximal humerus. Keywords: Noninvasive treatment, Proximal humerus fractures, Osteoporosis Neers classification, Related functional aftermath, Functional outcome